Review of Microphone-Based Contactless Vital Signs Monitoring Systems - AMORAN, Abiodun Ernest; BISMOR, Dariusz (Archives of Acoustics, 2025)
Microphones are sensors common to a variety of the Internet of Things (IoT) and healthcare applications. Many examples have proved that microphones can be useful in detecting, e.g., abnormal breathing rates. There are already applications that serve this purpose, e.g., respiratory acoustic monitoring, ResApp, etc. Breath signal was studied using a range of technologies and sensors, including the most common: radar, accelerometer, wearables, and so on. The majority of these sensors are attached to the body of a monitored person. However, the emergence of COVID-19 has drawn particular attention to the importance of using non-contact technologies for monitoring breath signals and other vital signs. This paper presents a comprehensive review of microphone-based non-contact vital sign monitoring, including the methodologies and concepts, while identifying new research gaps and opportunities for the future studies.